2013
DOI: 10.1097/pec.0b013e3182a21a23
|View full text |Cite
|
Sign up to set email alerts
|

What Role Does Body Mass Index Play in Hospital Admission Rates From the Pediatric Emergency Department?

Abstract: Underweight children (BMI ≤5%) have an increased risk of hospitalization from the emergency department, even when adjusted for age and sex. In particular, hospitalization among underweight patients was increased for those patients with respiratory infections and fractures. No difference was seen between admission rates of overweight (BMI ≥85%) or obese (BMI ≥95%) patients from those of normal-weight patients. This warrants the need to counsel patients and their families on the dangers not only of obesity, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 5 publications
0
16
1
Order By: Relevance
“…18 Little is known about the prevalence of underweight percentage among burn patients specifically, nor the effects of this nutritional marker on patient outcomes in the developing world, with US studies giving mixed results. [19][20][21] Despite hypothesizing that underweight status may correlate with poor outcomes in our study, we found that underweight did not have a predictive relationship with mortality.…”
Section: Our Patients and Western Patientscontrasting
confidence: 77%
“…18 Little is known about the prevalence of underweight percentage among burn patients specifically, nor the effects of this nutritional marker on patient outcomes in the developing world, with US studies giving mixed results. [19][20][21] Despite hypothesizing that underweight status may correlate with poor outcomes in our study, we found that underweight did not have a predictive relationship with mortality.…”
Section: Our Patients and Western Patientscontrasting
confidence: 77%
“…Six studies that included ±1000 patients recruited in different hospital settings, therefore better representing the “true” prevalence for the respective geographical locations have been reported. Wyrik et al [64] from the US reported a prevalence of malnutrition of 24.5% based on ≤5%ile BMI. However, as the population studied was from emergency departments of tertiary care facilities there is a likelihood of selection bias.…”
Section: Prevalence Of Acute Malnutritionmentioning
confidence: 99%
“… 44 56 In addition, one study reported that 14.5% of obese or overweight children were admitted, compared with 16.5% normal-weight children. 42 For overweight children, one study reported a significant decrease 56 while one reported a non-significant decrease 37 in admissions compared with normal-weight children.…”
Section: Resultsmentioning
confidence: 99%